Risks associated with tandem release of large and small ladybirds (Coleoptera: Coccinellidae) in heterospecific aphidophagous guilds. Issue 1 (23rd December 2013) - Omkar; Mishra, Geetanjali; Kumar, Bhupendra; Singh, Neha; Pandey, Garima
Abstract Multiple interactions occurring within aphidophagous guilds determine their final predation outcomes, i.e., antagonistic, additive, or synergistic. Based on these predatory outcomes, the suitability of guilds in suppressing aphid pests is determined. The present study assesses the efficacy of 11 guilds, formed from both larval and adult stages of four locally abundant aphidophagous coccinellids (Coleoptera: Coccinellidae), while exploiting the pea aphid, Acyrthosiphon pisum Harris (Hemiptera: Aphididae). The observed antagonistic effects within these guilds are resultants of enhanced predator–predator interactions due to the size and diversity of guild predators. Smaller ladybird predators maintained their usual body mass, probably by increasing their conversion efficiencies to compensate for their reduced prey consumption. However, larger ladybirds reported loss in their body mass, owing to their higher energy needs. The overall guild conversion efficiencies and growth rates were reduced. Among the experimental guilds, the observed prey mortalities were relatively higher in two-predator guilds, and within these two-predator combinations, the higher prey mortalities were recorded in those guilds where Coccinella septempunctata was one of the predators.